Characterization of 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate synthase (HDS) gene from Ginkgo biloba - Kim, Sang-Min; Kim, Soo-Un (SPRINGER, 2010)
Diterpene trilactone ginkgolides, one of the major constituents of Ginkgo biloba extract, have shown interesting bioactivities including platelet-activating factor antagonistic activity. 1-Hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate synthase (HDS), converting 2-C-methyl-d-erythritol-2,4-cyclodiphosphate into 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate, is the penultimate enzyme of the seven-step 2-C-methyl-d-erythritol 4-phosphate pathway that supplies building blocks for plant isoprenoids of plastid origin such as ginkgolides and carotenoids. Here, we report on the isolation and characterization of the full-length cDNA encoding HDS (GbHDS, GenBank accession number: DQ251630) from G. biloba. Full-length cDNA of GbHDS, 2,763 bp long, contained an ORF of 2,226 bp encoding a protein composed of 741 amino acids. The theoretical molecular weight and pI of the deduced mature GbHDS of 679 amino acid residues are 75.6 kDa and 5.5, respectively. From 2 weeks after initiation of the culture onward, transcription level of this gene in the ginkgo embryo roots increased to about two times higher than that in the leaves. GbHDS was predicted to possess chloroplast transit peptide of 62 amino acid residues, suggesting its putative localization in the plastids. The transient gene expression in Arabidopsis protoplasts confirmed that the transit peptide was capable of delivering the GbHDS protein from the cytosol into the chloroplasts. The isolation and characterization of GbHDS gene enabled us to further understand the role of GbHDS in the terpenoid biosynthesis in G. biloba.
Keywords: 1-DEOXY-D-XYLULOSE 5-PHOSPHATE SYNTHASE; ISOPRENOID BIOSYNTHESIS; PATHWAY; CLONING; TRANSFORMATION; TRANSCRIPTION; ACCUMULATION; TRANSPORT; GCPE